2023
DOI: 10.1177/23259671231192127
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Injuries Associated With ACL Rupture in Elite Professional Alpine Ski Racers and Soccer Players: A Comparative Study With Propensity Score Matching Analysis

Luca Farinelli,
Robert Csapo,
Amit Meena
et al.

Abstract: Background: For elite professional soccer players and alpine skiers, injuries associated with anterior cruciate ligament (ACL) rupture, such as meniscal, cartilage, or collateral ligament lesions, could result in a delayed return to sport compared with isolated ACL injury. Purpose/Hypothesis: The purpose of the study was to provide a detailed description of associated injuries at the time of primary ACL reconstruction in elite soccer players and alpine skiers. It was hypothesized that soccer players and skiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…34 These described scenarios and mechanisms could also theoretically lead to meniscus tears as the prevalence of concomitant meniscal pathology in soccer players who rupture their ACLs has been found to be as high as 86%. 35 Though understudied, repetitive hyperextension with kicking may also cause a specific pattern of meniscal injury in soccer players, as numerous case series have, since, demonstrated a specific pattern of pathology in the anterior horn of the lateral meniscus in soccer players. [36][37][38]…”
Section: Meniscal Anatomy Biomechanics and Mechanisms Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…34 These described scenarios and mechanisms could also theoretically lead to meniscus tears as the prevalence of concomitant meniscal pathology in soccer players who rupture their ACLs has been found to be as high as 86%. 35 Though understudied, repetitive hyperextension with kicking may also cause a specific pattern of meniscal injury in soccer players, as numerous case series have, since, demonstrated a specific pattern of pathology in the anterior horn of the lateral meniscus in soccer players. [36][37][38]…”
Section: Meniscal Anatomy Biomechanics and Mechanisms Of Injurymentioning
confidence: 99%
“…While there are no studies examining mechanisms of isolated meniscus tears in soccer players specifically, a systematic review found that knee valgus loading when “pressing and tackling,” “being tackled,” “regaining balance after kicking,” or “landing from a jump” were the most common mechanisms of ACL tears 34 . These described scenarios and mechanisms could also theoretically lead to meniscus tears as the prevalence of concomitant meniscal pathology in soccer players who rupture their ACLs has been found to be as high as 86% 35 . Though understudied, repetitive hyperextension with kicking may also cause a specific pattern of meniscal injury in soccer players, as numerous case series have, since, demonstrated a specific pattern of pathology in the anterior horn of the lateral meniscus in soccer players 36–38 …”
Section: Meniscal Anatomy Biomechanics and Mechanisms Of Injurymentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) rupture represents a serious injury for athletes [10]. It could be associated to meniscal, cartilage and collateral ligament lesions and represent a common cause of rotatory knee instability [9,13,33]. The ACL provides restraint to anterior translation and internal rotation of the tibia relative to the femur [16,38,50].…”
Section: Introductionmentioning
confidence: 99%